Measuring the Psychological Security of Urban Residents: Construction and Validation of a New Scale - Wang, Jiaqi; Long, Ruyin; Chen, Hong; Li, Qianwen (Frontiers in Psychology, 2019)
With the acceleration of urbanization in developing countries, resources relating to medical care and the environment are becoming increasingly scarce, and the negative spillover effects brought about by scientific and technological progress have also significantly increased the pressure on urban residents. The psychological security of urban residents has recently undergone significant change. This paper introduces psychological security into the area of urban residents’ lives, defines the concept of urban residents’ psychological security, and presents the development and validation of the Urban Residents Psychological Security Scale (URPS). By considering psychological indicators, this paper supplements our knowledge on environmental indicators such as the risk perception of environmental pollution and climate change, and social indicators such as urban belongingness and the risk perception of technology which verifies the negative spillover effects of technological development. Based on a literature search and consideration of grounded theory (25 urban residents’ in-depth interview records), the psychological security of urban residents is divided into three dimensions: self-psychological security, social environmental security, and natural environmental security, consisting of 20 items. In this study, 802 questionnaires were completed by participants. We determined that the URPS scale has good reliability and validity using exploratory factor analysis and confirmatory factor analysis, and conclude that the scale can be used as an effective measurement tool for urban residents’ psychological security. The development of this scale has important theoretical and practical significance in helping city managers better understand the residents’ demands and to monitor the implementation effects of policies.